Molecular Biology of Medulloblastoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Current methods of diagnosis and treatment of medulloblastoma, and the influence of new biological advances in the development of more effective and less toxic therapies are reviewed by researchers at Children's National Medical Center, The George Washington University, Washington, DC.